INTERNATIONAL CONFERENCE «TIMELY PROBLEMS OF MODERN VACCINAL PREVENTION IN RUSSIA» - A.A. Автор (Вопросы современной педиатрии, 2011)
(Voprosy sovremennoi pediatrii — Current Pediatrics. — 2011; 10 (5): 178–179.)